Germination and survival of five Cactace species from The Tehuacan Valley: Implications for their conservation - Alvarez Aguirre, Maria Guadalupe; Montaña, Carlos (Instituto de Ecología, A.C., 1997)
Germination and establishment of five cacti species growing in the Valley of Zapotitlán de las Salinas (Puebla) were studied. The species, all endemic to Mexico and whose saplings and juveniles are used as ornamental plants, were Cephalocereus chrysacanthus, Cephalocereus hoppenstedtii, Ferocactus latispinus, Stenocereus stellatus and Wilcoxia viperina. Aiming to develop conservative management practices, the objective of the work was to assess if the establishment requirements of the species could be provided by simple cultivation methods that can be economically and technologically affordable by local peasants.